The Gender Reference Point Gap - Nathan Kettlewell; Jonathan Levy; Agnieszka Tymula; Xueting Wang (Institute of Labor Economics (IZA), 2023)
Studies have frequently found that women are more risk averse than men. In this paper, we depart from usual practice in economics that treats risk attitude as a primitive, and instead adopt a neuroeconomic approach where risk attitude is determined by the reference point which can be easily estimated using standard econometric methods. We then evaluate whether there is a gender difference in the reference point, explaining the gender difference in risk aversion observed using traditional approaches. In our study, women make riskier choices less frequently than men. Compared to men, we find that women on average have a significantly lower reference point. By acknowledging the reference point as a potential source of gender inequality, we can begin a new discussion on how to address this important issue.
Keywords: C90; D87; D91; J16; 330; reference point; risk attitude; neuroeconomics; gender; inequality; experiment